El silencio administrativo en la Ley 39/2015 desde la jurisprudencia constitucional. (A propósito de la STC 7072018, de 21 de junio) - José Antonio Razquin Lizarraga (Revista Vasca de Administración Pública)
The constitutional jurisprudence has considered from the perspective of the allocation of powers the new regulation of administrative silence as set out by Act 39/2015, of October 1, on the Common Administrative Procedure of Public Administrations. In light of this doctrine, this paper studies the novelties upon the restriction of the general rule of the positive silence and the addition of a new case for negative silence, together with the prohibition clause regarding the acquisition of faculties or rights due to the silence in breach of legality.